La dimensión comunicativa del paisaje. Una propuesta teórica y aplicada - Nogué, Joan; de San Eugenio Vela, Jordi (Revista de Geografía Norte Grande, 2021)
The fusion of knowledge, the interrelationship of disciplines and, finally, the interaction of learning fields, provide new challenges for an auto denominated global society. The contemporary value of landscape, linked to the patent commodification of culture, the commercial construction of identities, the triumph of inauthenticity, of the induced representation or the economy of symbolism, open up great prospects for studying the symbolic value of landscape. The rapprochement of geographical praxis to the study of space intangibles, linked to the discovery of emotional geographies, besides the growing interest of communication a science for the territorial discourse, allow us to envisage a communicative study of landscape based on a fusion of geography and communicational knowledge. The balancing of the variables: geography, landscape, emotion and communication, enables to progress towards analysing the emotionalisation of space to discern its intangible value, which emerges from the application of different communication techniques